QIYAS OF MUZARAAH HADITH WITH FISHERIES SECTOR AND IT’S CONTRIBUTION TO WELFARE OF FISHERMEN - Ja'far Assagaf (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
This research background is the condition of Indonesian small fishermen who are generally still below the minimum wage income line. through the qiyas (analoqy) method, the muzara'ah hadith can be applied in the fisheries sector with the aim that small fishermen income is better than before. the results of this study indicate that with the distribution system as muzara'ah that is profit sharing according to the percentage, small fishermen will be more prosperous than the wage or payment system.